PRESIDENT JOKOWIÃ¢â‚¬â„¢S CAMPAIGN SPEECH ON Ã¢â‚¬Å“MEWUJUDKAN JAKARTA BARUÃ¢â‚¬Â THE ANALYSIS OF ILLOCUTIONARY ACT - SUDARMAWAN, I PUTU YUDI (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2018)
AbstractSpeech is one of the important steps during campaign process to attract voters in the political election. The candidates choose the proper diction to make the voters believe about their future programs and have faith to the person itself in making the programs come to real. This study attempts to analyze political campaign speech of Jokowi for Jakarta gubernatorial election. Revealing Jokowiâ??s intention and purpose in his campaign speech becomes the objective of this study. This study helps politicians to learn and investigate about the political strategy in campaigning, and for Jakarta gubernatorial election voters, it might help in monitoring Jokowiâ??s programs in the campaign and its realization. This study applies qualitative research method approach. The writer uses YouTube as media to collect the data. In analyzing the data, the writer uses Speech Act Theory, especially Illocutionary Act that is proposed by John Searle. The finding of the study, the writer found that Jokowi mostly use representatives speech act in his campaign speech, since the representatives speech act deals with the speakerâ??s belief. During his campaign speech, Jokowi states his believes that there must be some improvements for Jakarta by using representatives act.Â Keywords: Campaign; Speech; Illocutionary Act; Â AbstrakPidato adalah salah satu langkah penting selama proses kampanye untuk menarik pemilih dalam pemilihan politik. Para kandidat memilih diksi yang tepat untuk membuat para pemilih percaya tentang program masa depan mereka dan memiliki keyakinan kepada orang itu sendiri dalam membuat program menjadi nyata. Penelitian ini mencoba menganalisis pidato kampanye politik Jokowi untuk pemilihan gubernur DKI Jakarta. Mengungkap niat dan tujuan Jokowi dalam pidato kampanyenya menjadi tujuan dari penelitian ini. Studi ini membantu politisi untuk belajar dan menyelidiki tentang strategi politik dalam kampanye, dan untuk pemilih pemilihan gubernur Jakarta, mungkin membantu dalam memantau program Jokowi dalam kampanye dan realisasinya. Penelitian ini menggunakan pendekatan metode penelitian kualitatif. Penulis menggunakan YouTube sebagai media untuk mengumpulkan data. Dalam menganalisis data, penulis menggunakan Speech Act Theory, khususnya Illocutionary Act yang diusulkan oleh John Searle. Temuan dari penelitian ini, penulis menemukan bahwa Jokowi kebanyakan menggunakan kata-kata perwakilan dalam pidato kampanyenya, karena pidato perwakilan berbicara tentang kepercayaan pembicara. Selama pidato kampanyenya, Jokowi menyatakan keyakinannya bahwa harus ada beberapa perbaikan untuk Jakarta Dengan Menggunakan Aksi perwakilan.Â Kata Kunci: Kampanye, Illocutianary Act